2007
DOI: 10.1007/s11064-007-9412-z
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of NMDA Receptor Subunits in Cerebral Cortex and Hippocampus is Differentially Increased by Administration of Endobain E, a Na+, K+-ATPase Inhibitor

Abstract: Previous studies showed that endobain E, an endogenous Na+, K+-ATPase inhibitor, decreases dizocilpine binding to NMDA receptor in isolated membranes. The effect of endobain E on expression of NMDA receptor subunits in membranes of rat cerebral cortex and hippocampus was analyzed by Western blot. Two days after administration of 10 mul endobain E (1 microl = 29 mg fresh tissue) NR1 subunit expression enhanced 5-fold and 2.5-fold in cerebral cortex and hippocampus, respectively. NR2A subunit expression increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…, K ? -ATPase inhibitor, endobain E, differentially modifies the expression of glutamatergic ionotropic NMDA receptor subunits [52].…”
Section: Discussionmentioning
confidence: 99%
“…, K ? -ATPase inhibitor, endobain E, differentially modifies the expression of glutamatergic ionotropic NMDA receptor subunits [52].…”
Section: Discussionmentioning
confidence: 99%
“…Taken jointly, findings indicated that ouabain and endogenous inhibitor endobain E differentially increased expression of NMDA receptor subunits [19,20] and that this effect was concomitant with changes in Na ? , K ?…”
Section: Discussionmentioning
confidence: 88%
“…-ATPase a3 subunit expression enhance in cerebral cortex and hippocampus and that the effect was dose-dependent. It is of interest to recall that the doses of endobain E employed herein (1 ll and 10 ll) are the same which proved effective to produce statistically significant increases in the expression of most NMDA subunits in cerebral cortex and hippocampus [19].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations